2018
DOI: 10.1002/wrna.1498
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional RNA‐binding proteins step into the virus–host battlefront

Abstract: The crucial participation of cellular RNA-binding proteins (RBPs) in virtually all steps of virus infection has been known for decades. However, most of the studies characterizing this phenomenon have focused on well-established RBPs harboring classical RNA-binding domains (RBDs). Recent proteome-wide approaches have greatly expanded the census of RBPs, discovering hundreds of proteins that interact with RNA through unconventional RBDs. These domains include protein-protein interaction platforms, enzymatic cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 198 publications
0
92
0
1
Order By: Relevance
“…Viral proteins were the only class enriched in extremely high positively charged segments (charge ≥ + 17) when compared to the overall proteome (1B-inset with p-values). Positively charged protein stretches can be involved in diverse roles, such as membrane interaction, DNA or RNA binding, and cellular localization signaling (25). All these functions are important for virus replication and must contribute to the charge distribution profile of the viral protein dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Viral proteins were the only class enriched in extremely high positively charged segments (charge ≥ + 17) when compared to the overall proteome (1B-inset with p-values). Positively charged protein stretches can be involved in diverse roles, such as membrane interaction, DNA or RNA binding, and cellular localization signaling (25). All these functions are important for virus replication and must contribute to the charge distribution profile of the viral protein dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, overexpression of both TRIM25-eGFP and TRIM56-eGFP strongly reduced SINV fitness (Figure 7B), confirming that these RBPs are part of the cell’s molecular arsenal to restrict virus infection. 160 out of the 245 SINV-responsive RBPs lack previous connections to virus infection, based on our recent analysis of protein annotation and automated literature mining (Garcia-Moreno et al, 2018). Hence, our dataset likely contains numerous pro- and antiviral RBPs to be discovered.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, specialised RBPs are at the frontline of cellular antiviral defences, detecting pathogen-associated molecular patterns (PAMPs) such as double stranded RNA or RNAs with 5’ tri-phosphate ends (Barbalat et al, 2011; Garcia et al, 2006; Rehwinkel and Reis e Sousa, 2013; Vladimer et al, 2014). Since RBPs are crucial for both the viral biological cycle and the host antiviral defences (Garcia-Moreno et al, 2018), virus infection thus represents an optimal scenario to assess the RBPome dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Many This is a provisional file, not the final typeset article cellular RNA-binding proteins (RBPs) containing well-established RNA-binding domains (RBDs) are known to be critical for infection by different viruses. Recently, 472 RBPs were reviewed for their linkage to viruses (Garcia-Moreno et al, 2018). It has been demonstrated that G-quadruplex formation in HIV-1 viral genome stalls RNA polymerase, thereby limiting viral replication in host cells.…”
Section: Discussionmentioning
confidence: 99%